Pengaruh Sistem Pengendalian Intern Pemungutan Pajak Hotel terhadap Efektivitas Penerimaan Pajak Hotel Di Kabupaten Garut pada Badan Pendapatan Daerah Kabupaten Garut - Desi Qoriah (Fakultas Ekonomi Universitas Garut, 2017)
This study entitled: The Effect of Hotel Tax Collection Internal Control System on the Effectiveness of Hotel Tax Receipts in Garut Regency at the Regional Revenue Agency of Garut Regency. The purpose of this study was to determine how the influence of the Hotel Tax Collection Internal Control System on the Effectiveness of Hotel Taxes in Garut Regency on Regional Revenue Bodies. The method used in this research is quantitative descriptive method. The data collection technique uses library research, interviews, questionnaires and documentation, while the data processing techniques are performed using correlation analysis, simple regression analysis and the coefficient of determination. The results showed that the Hotel Tax Collection Internal Control System at the Regional Revenue Agency (BAPENDA) Garut Regency has a significant effect on the Effectiveness of Hotel Tax Receipts in Garut Regency.